2020
DOI: 10.1103/physreva.101.012337
|View full text |Cite
|
Sign up to set email alerts
|

Generation of quantum entangled states of multiple groups of qubits distributed in multiple cavities

Abstract: Provided that cavities are initially in a Greenberger-Horne-Zeilinger (GHZ) entangled state, we show that GHZ states of N -group qubits distributed in N cavities can be created via a 3-step operation. The GHZ states of the N -group qubits are generated by using N -group qutrits placed in the N cavities. Here, "qutrit" refers to a three-level quantum system with the two lowest levels representing a qubit while the third level acting as an intermediate state necessary for the GHZ state creation. This proposal do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In the past years, theoretical schemes for preparing multi-SC-qubit GHZ entangled states have been proposed [102][103][104][105][106][107], and the experimental production of GHZ entangled states with up to 18 SC qubits has been reported [12,18,19,[30][31][32][33][34]. The initial state of the whole system is thus given by…”
Section: B Generation Of Hybrid Ghz Entangled States With M Sc Qubits...mentioning
confidence: 99%
“…In the past years, theoretical schemes for preparing multi-SC-qubit GHZ entangled states have been proposed [102][103][104][105][106][107], and the experimental production of GHZ entangled states with up to 18 SC qubits has been reported [12,18,19,[30][31][32][33][34]. The initial state of the whole system is thus given by…”
Section: B Generation Of Hybrid Ghz Entangled States With M Sc Qubits...mentioning
confidence: 99%
“…Our physical interpretations of the HD-information and the Wehrl entropy-mixedness in qubit-cavity systems linked by a waveguide mode contribute to updating more potential applications for distributed quantum information processing that are based on realizing a multi-target-qubit unconventional geometric phase gate in a multi-cavity system [ 40 ], as well as entanglement stabilization protocols between two superconducting qubits that are coupled to distant cavities [ 41 ] and the architecture of the cavity-based quantum network [ 42 ]. It is found that certain coupling parameters of the exciton-cavity and the fiber-cavity interactions control the effects of the optical linear medium and the environment, which are major obstacles to the applications of the quantum information technology.…”
Section: Husimi Distribution (Hd)mentioning
confidence: 99%
“…This is of importance to the conception of quantum networks based on distributed quantum nodes (qubits) for the storage and manipulation of quantum data [ 32 , 38 , 39 ]. Recent applications for qubit-cavity systems are based on realizing a multi-target-qubit unconventional geometric phase gate [ 40 ], entanglement stabilization protocols [ 41 ], and the network architecture [ 42 ]. We are also interested to analyze the generation and robustness of the phase space information and the mixedness in the cavity-fiber systems depending on the Husimi distribution and Wehrl entropy quantifiers.…”
Section: Introductionmentioning
confidence: 99%
“…This system allows quantum information to be encoded into two low-energy levels, with the transition being indirectly realized through a high-energy one. Some common three-level physical systems, such as nitrogen vacancy centers [24][25][26][27] and trapped ions [28][29][30], have been developed to reduce the unfavorable impact of decoherence on qubits.…”
Section: Introductionmentioning
confidence: 99%